PENGARUH CITRA PERUSAHAAN DAN KUALITAS PELAYANAAN TERHADAP LOYALITAS PELANGGAN PADA HOTEL DYAN GRAHA PEKANBARU - Tobia Sutejo Pandiangan; Endang Sutrisna (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
In the current era of globalization, many significant changes in various aspects of human life, The change aims to meet the human needs of increasingly increasing in aspects of life. In this case the progress of a country must be followed by the contribution of the service sector to the economy. The number of businesses that exist increasingly make many companies interested in competing.The population in this study are customers who stay at Hotel Dyan Graha Pekanbaru with sampling of 100 people calculated by using slovin formula. The sampling technique is done by purposive sampling. Data collection of research in the form of primary data by using qusioner as research instrument, data analysis used is by using multiple linear regression analysis with the help of program of SPSS.From the results of tests conducted show that corporate image and service quality have a positive effect on customer loyalty. Where the value of determination coefficient (R2) shows that the variable of corporate image and service quality contributed to customer loyalty of 48.2% while the rest of 51.2% influenced by other variables not included in this research model.Keywords: Corporate Image, Service Quality, and Customer Loyalty